Association of Occlusal Force with Cognition in Independent Older Japanese People. (April 2016) - Takeshita, H.; Ikebe, K.; Gondo, Y.; Inagaki, H.; Masui, Y.; Inomata, C.; Mihara, Y.; Uota, M.; Matsuda, K.; Kamide, K.; Takahashi, R.; Arai, Y.; et al.
Recent longitudinal studies have shown the influence of multiple tooth loss on cognitive impairment, and earlier studies suggested that periodontal disease was related to cognitive decline. Tooth loss is associated with reduced masticatory function, which may affect stimulation of the central nervous system and dietary intake. Although some studies have reported a relationship between chewing ability and cognitive function, no studies have examined this area in terms of objective oral function. The aim of this study was to examine the association of occlusal force with cognitive decline in the preclinical stage among older people with higher-level functional capacity. This cross-sectional study for community-dwelling older people living in urban and rural areas in Japan examined 994 persons in the 70-y group (age range, 69–71 y) and 968 persons in the 80-y group (age range, 79–81 y). Retention of higher-level competence was defined according to the Tokyo Metropolitan Institute of Gerontology Index of Competence. Cognitive function was measured with the Japanese version of the Montreal Cognitive Assessment (MoCA-J). Oral status and function were assessed by the number of remaining teeth, periodontal pocket depth, and maximal occlusal force. Associations between the MoCA-J score and occlusal force were examined by bivariate and multivariate analysis. Approximately one-half of the participants retained higher-level functional capacity and were included in the analysis. Multiple regression analysis showed that occlusal force was significantly related to cognitive function after controlling for possible predictors including age, sex, socioeconomic status, medical condition, and handgrip strength. The number of remaining teeth and periodontal pocket depth were not significantly associated with cognitive function. Among community-dwelling older people with retained competence, maximal occlusal force was positively associated with their cognitive function. These results suggest that oral function might be a predictor for preclinical cognitive decline. Knowledge Transfer Statement : Multiple regression analysis showed that occlusal force was significantly related to cognition after controlling for possible predictors including handgrip strength as an indicator of general muscle strength, suggesting the independence of oral function. The number of remaining teeth did not have this association. The majority of older people have lost teeth and have received prosthodontic treatment, and their occlusal force is determined not only by the number of remaining teeth but also by prosthetic rehabilitation. These results can be used by clinicians focusing on prevention of tooth loss among the entire population, as well as to encourage partially edentulous and fully edentulous patients to restore their oral function with prostheses in order to eliminate a possible risk factor for cognitive impairment.